2006
DOI: 10.2116/analsci.22.1387
|View full text |Cite
|
Sign up to set email alerts
|

Selective Extraction of Uranium from a Mixture of Metal or Metal Oxides by a Tri-n-butylphosphate Complex with HNO3 and H2O in Supercritical CO2

Abstract: Several studies have been performed to extract actinides from the spent nuclear fuels using supercritical fluids. [1][2][3][4][5][6][7][8] Among these studies, a method has been studied in which decladded spent fuels are "directly" treated by the supercritical fluid, a single-phase mixture of HNO3, H2O and tri-n-butylphosphate (TBP) in supercritical carbon dioxide (SC-CO2). [9][10][11] Here, "directly" means "without a dissolution process". For the decladding process, the spent fuel is treated thermally in air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Shimada et al [240] studied the decontamination nature of the reactive extraction of uranium in the presence of some metal chemicals using a single-phase mixture of HNO 3 , H 2 O and tri-nbutylphosphate in supercritical carbon dioxide. They measured the decontamination factors (DFs) of the metals from their mixture with U, as a function of the molecular ratio of U to TBP in the extracted complex.…”
Section: Extraction With Solvents and Supercritical Fluidsmentioning
confidence: 99%
“…Shimada et al [240] studied the decontamination nature of the reactive extraction of uranium in the presence of some metal chemicals using a single-phase mixture of HNO 3 , H 2 O and tri-nbutylphosphate in supercritical carbon dioxide. They measured the decontamination factors (DFs) of the metals from their mixture with U, as a function of the molecular ratio of U to TBP in the extracted complex.…”
Section: Extraction With Solvents and Supercritical Fluidsmentioning
confidence: 99%
“…Several studies have been reported on SFE of actinides and lanthanides with TBP·HNO 3 adduct from various matrices viz. assorted radioactive waste matrices and spent nuclear fuels from different nuclear reactors (Shadrin et al, 2008;Zhu et al, 2012;Shamsipur et al, 2001;Shimada et al, 2006). Uranium present in spent nuclear fuel has been selectively recovered with good separation factors from fission products by SFE followed by counter current chromatographic separation (Myasoedov et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that MA(III), Ln(III), and uranyl ion (U(VI)) can be extracted from solid or liquid materials to scCO 2 as soluble complexes with chelating ligands such as organophosphorus compounds and b-diketones [7][8][9][10][11][12]. The solubility of various metal complexes including U(VI) in scCO 2 has been investigated, and the results have indicated that fluorination of coordinated ligands drastically enhances the solubility of metal complexes by several orders of magnitude compared with non-fluorinated analogues [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%